2012
DOI: 10.1016/j.polymdegradstab.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ionizing radiation on physicochemical and biological properties of an amphiphilic macromolecule

Abstract: An amphiphilic macromolecule (AM) was exposed to ionizing radiation (both electron beam and gamma) at doses of 25 kGy and 50 kGy to study the impact of these sterilization methods on the physicochemical properties and bioactivity of the AM. Proton nuclear magnetic resonance and gel permeation chromatography were used to determine the chemical structure and molecular weight, respectively. Size and zeta potential of the micelles formed from AMs in aqueous media were evaluated by dynamic light scattering. Bioacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Using ionizing radiation in the terminal sterilization process is advantageous, because the gamma rays may penetrate up to 300 mm into materials due to their mass absence, facilitating their extensive use in processing larger product quantities at once. Moreover, these attributes allow employing at final packaging, avoiding further contamination and excessive handling [ 75 , 94 ]. However, this technique’s main disadvantage is the difficulty of gaining access to gamma irradiators.…”
Section: Ionizing Radiationmentioning
confidence: 99%
“…Using ionizing radiation in the terminal sterilization process is advantageous, because the gamma rays may penetrate up to 300 mm into materials due to their mass absence, facilitating their extensive use in processing larger product quantities at once. Moreover, these attributes allow employing at final packaging, avoiding further contamination and excessive handling [ 75 , 94 ]. However, this technique’s main disadvantage is the difficulty of gaining access to gamma irradiators.…”
Section: Ionizing Radiationmentioning
confidence: 99%
“…The SBAP applications discussed thus far have involved thermodynamic assemblies, including polymeric micelles. When SBAP concentrations exceed their CMC, SBAPs spontaneously self-assemble into such micelles. , SBAP micelles can be beneficial delivery systems because their hydrophilic shell helps prevent nonspecific protein adsorption while their nanoscale size can reduce renal clearance and RES uptake. , Furthermore, SBAPs administered in this micelle form have demonstrated the ability to inhibit oxLDL uptake by macrophages, indicating their potential use as antiatherosclerotic therapies. Despite these advantageous properties enabling SBAPs to serve as both bioactives and delivery systems, research has suggested that polymeric micelle stability can be compromised in physiological environments. …”
Section: Sbap-based Nanoparticles To Enhance Serum Stabilitymentioning
confidence: 99%
“…[23][24][25][26] These AMs exhibit low CMC values (~10 -7 M), indicating that the micelles can maintain their integrity upon dilution when circulated in physiological conditions. 27,28 With good structural tunability, the AMs not only have shown promise in solubilizing various drug molecules and enhancing preferential cellular uptake [29][30][31][32] but also possess intriguing anti-atherosclerotic activity. 33 Considering the relatively simple structure, ease of synthesis, biocompatibility, and structural tunability, 34 the sugar-based AMs are ideal candidates for development into pH-responsive systems for drug delivery applications.…”
Section: Introductionmentioning
confidence: 99%